Manual handling in health and social care : an A-Z of law and practice - Mandelstam, Michael, 1956- (Jessica Kingsley, 2002)
A practical understanding of the law is essential for all those involved in the manual handling of adults and children (as patients, clients or pupils), whether in 'hands-on', managing, commissioning or advisory roles. To this end, Manual Handling in Health and Social Care presents an accessible overview of manual handling legislation, legal case law, national guidance, policy and practice. Applicable primarily to England, Scotland and Wales, it covers both employee safety under the Manual Handling Operations Regulations and wider health and safety at work legislation, and also patient and cli.